Stiftungen zwischen Politik und Wirtschaft: Geschichte und Gegenwart im Dialog - Reden, Sitta von (Historische Zeitschrift, 2015)
Gifts, donations, and charity help shape society and can be regarded as virtual social and political constants. For the first time, this volume uses a range of scholarly perspectives and cultural comparison to examine the tensions, conflicts, and the social and religious transformation processes that have shaped philanthropy in European and non-European societies to this day.
Description based upon print version of record
Keywords: Electronic books; Konferenzschrift; Geschichte; Stiftung